2007
DOI: 10.1164/rccm.200609-1354oc
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pulmonary Function and Sputum Biomarkers in Cystic Fibrosis

Abstract: These data support the role of sputum biomarkers as correlates of disease severity in a diverse CF population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
193
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(207 citation statements)
references
References 24 publications
13
193
1
Order By: Relevance
“…Desmosine and isodesmosine, amino acids found exclusively in cross-linked elastin and released by HLE-mediated proteolysis, are present at increased concentrations in the urine of CF patients when compared with healthy control subjects [32,41,42]. Patients with CF have high levels of active HLE in their sputum particularly during infectious respiratory exacerbations e levels of active HLE detected in the bronchoalveolar lavage uid of CF patients correlate signi cantly with pulmonary function indices of the severity of lung disease such as the FEV1 and the ratio of FEV1/FVC [14,32,44]. Lung secretion HLE is clearly an attractive surrogate marker for CF lung disease since it directly relates to an important pathogenic pathway in CF.…”
Section: Discussionmentioning
confidence: 99%
“…Desmosine and isodesmosine, amino acids found exclusively in cross-linked elastin and released by HLE-mediated proteolysis, are present at increased concentrations in the urine of CF patients when compared with healthy control subjects [32,41,42]. Patients with CF have high levels of active HLE in their sputum particularly during infectious respiratory exacerbations e levels of active HLE detected in the bronchoalveolar lavage uid of CF patients correlate signi cantly with pulmonary function indices of the severity of lung disease such as the FEV1 and the ratio of FEV1/FVC [14,32,44]. Lung secretion HLE is clearly an attractive surrogate marker for CF lung disease since it directly relates to an important pathogenic pathway in CF.…”
Section: Discussionmentioning
confidence: 99%
“…Airway inflammation is thought to be an independent risk factor for lung function decline and biomarkers of inflammation could potentially be used to define an at-risk population (15). Previous cross-sectional studies have provided evidence that sputum neutrophil elastase (NE) levels are higher in patients with severe lung disease (16) and elastase burden in bronchoalveolar lavage is correlated to lower lung function and bronchiectasis in infants with CF (17). In a longitudinal cohort study Sagel and colleagues demonstrated that elevated neutrophil elastase concentrations in sputum predict subsequent lung function decline and that longitudinal changes in NE are correlated to evolution of lung function (18).…”
Section: Airway Inflammation In Cfmentioning
confidence: 99%
“…With the recent development of disease-modifying treatments for CF, there is a need for noninvasive techniques to monitor disease development and progression in young children [3,4]. While lung function tests offer an alternative to invasive surveillance, studies correlating disease outcomes and respiratory function have predominantly been limited to those using spirometry [5][6][7] or techniques that require sedation [8][9][10][11][12][13][14], and there have been relatively few studies in preschool-aged children [8,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%